Evaluation of renal function in patients with human immunodeficiency virus - Ederson dos Santos Costa; Déborah Éllen Pinheiro de Oliveira; Francilene de Sousa Vieira; Gleciane Costa de Sousa; Maria Edileuza Soares Moura (Rev Rene)
Objective: to evaluate the renal function of patients undergoing antiretroviral therapy.Methods: documentary, analytical and cross-sectional study with 150 Human Immunodeficiency Virus positive patients, using antiretroviral therapy, who had under gone exams of serum creatinine and abnormal urine elements and sediments, the glomerular filtration rate was calculated by the Chronic Kidney Disease Epidemiology Collaboration equation and renal dysfunction was stratified. Results: 11.3% of the participants presented a glomerular filtration rate of less than 90 ml/min/1.73 m². Of these, 8.0% had renal dysfunction stage 2, and 3.3%, in stage 3. The variables, older age and prolonged exposure to antiretroviral therapy were statistically significant for altering renal function. Conclusion:estimates of glomerular filtration rate by means of the Chronic Kidney Disease Epidemiology Collaboration equation proved to be an effective measure of early detection of renal function impairment in people living with Human Immunodeficiency Virus/Acquired immunodeficiency syndrome in the use of antiretroviral therapy